1999
DOI: 10.1046/j.1365-2141.1999.01338.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukaemic blasts differ from normal bone marrow mononuclear cells and CD34+ haemopoietic stem cells in their metabolism of cytosine arabinoside

Abstract: Different metabolites of cytosine arabinoside (AraC) contribute to its cytotoxicity including incorporation of AraCTP into DNA, the incorporation of AraUMP into RNA, inhibition of polymerase alpha and beta (AraCMP/CTP), an impairment of repair mechanisms (AraCTP), alterations of phospholipid metabolism (AraCDP-choline), a direct membrane interaction (AraC), the alteration of signal transduction pathways (AraCDP-choline, AraCTP) and the induction of apoptosis. Since little is known about the potential differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…As only a small percentage of cells in the cord blood samples were stem cells, our results could be misleading. Yet, no difference in the metabolism of ara-C has been found between CD34 + stem cells isolated by FACS and normal bone marrow mononuclear cells (Braess et al, 1999). Because mononuclear cells isolated from cord blood closely resemble the morphology of those from normal bone marrow they can provide a good surrogate for investigations of haematological toxicity (Ghielmini et al, 1997), particularly as they are far easier to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…As only a small percentage of cells in the cord blood samples were stem cells, our results could be misleading. Yet, no difference in the metabolism of ara-C has been found between CD34 + stem cells isolated by FACS and normal bone marrow mononuclear cells (Braess et al, 1999). Because mononuclear cells isolated from cord blood closely resemble the morphology of those from normal bone marrow they can provide a good surrogate for investigations of haematological toxicity (Ghielmini et al, 1997), particularly as they are far easier to obtain.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to imatinib-induced inhibition of proliferation since cytotoxicity of Ara-C may be affected by DNA repair capacity, proliferation rate, and cell cycle status. 39 Other studies 28,37 have reported that the combination of Ara-C and imatinib substantially decreased CML colony formation compared with imatinib or Ara-C alone but did not directly evaluate CD34 þ cell apoptosis. Inhibition of CFC growth may reflect effects on cell proliferation and differentiation in addition to apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitor used was AraC, following its widespread use in vaccinia virus molecular biology. AraC and its metabolites have been documented to inhibit DNA and RNA polymerases, ribonucleotide reductase, and DNA damage repair mechanisms (6) and to damage RNA and DNA into which it or its metabolites are incorporated (33). It may also influence some signal transduction pathways (53).…”
Section: Discussionmentioning
confidence: 99%